2018
DOI: 10.1016/j.quaint.2018.09.036
|View full text |Cite
|
Sign up to set email alerts
|

The small mammal fauna from the palaeolithic site Marathousa 1 (Greece)

Abstract: The lacustrine deposits exposed at the Lower Palaeolithic site Marathousa 1 (Megalopolis, S. Greece) and intercalated between lignite Seam II and III yielded a collection of small vertebrate remains. The assemblage includes fish and small mammals; the mammal assemblage encompasses a variety of species, dominated by voles (arvicolids) of the genera Arvicola and Microtus. Other rodents are represented by a dipod cf. Alactaga and a murid of the genus Apodemus. In addition, there is a number of insectivore remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Tourloukis et al (2018a) suggested two different intervals for the deposition of MAR-1, assigning the sequence between the base of UB9 and the top of UB2 to either the glacial Marine Isotope Stage (MIS) 12 (480-420 ka) or to MIS14 (560-530 ka) based on a combination of magnetostratigraphy of the Marathousa member, chronostratigraphical correlations, and classical oxygen isotope variability by Lisiecki and Raymo (2005). The MIS12 option is the preferred model, because it also agrees with the pMET-pIRIR dating method by Jacobs et al (2018) from the same outcrop, as well as with the small mammal biochronology by Doukas et al (2018) (Table 2). (Blackwell et al, 2018) published ESR data from the upper part of the MAR-1 sequence correlated with UB2 and UB4, respectively.…”
Section: Chronologymentioning
confidence: 97%
See 1 more Smart Citation
“…Tourloukis et al (2018a) suggested two different intervals for the deposition of MAR-1, assigning the sequence between the base of UB9 and the top of UB2 to either the glacial Marine Isotope Stage (MIS) 12 (480-420 ka) or to MIS14 (560-530 ka) based on a combination of magnetostratigraphy of the Marathousa member, chronostratigraphical correlations, and classical oxygen isotope variability by Lisiecki and Raymo (2005). The MIS12 option is the preferred model, because it also agrees with the pMET-pIRIR dating method by Jacobs et al (2018) from the same outcrop, as well as with the small mammal biochronology by Doukas et al (2018) (Table 2). (Blackwell et al, 2018) published ESR data from the upper part of the MAR-1 sequence correlated with UB2 and UB4, respectively.…”
Section: Chronologymentioning
confidence: 97%
“…It is located 60 m south of Area A and covers ∼78 m 2 at ∼350 m a.s.l. Both areas contain fossils of micro-and macro-fauna and flora such as hippos, elephants and rodents, as well as seeds, fruits, and charcoal (Doukas et al, 2018;Field et al, 2018;Konidaris et al, 2018;Michailidis et al, 2018). Karkanas et al (2018) subdivided the stratigraphy of MAR-1 into sedimentary units separated by an erosional contact into two major sequences, with the lower showing a coarsening upward and the upper a fining upward trend (Figure 3).…”
Section: Marathousa 1 Sedimentsmentioning
confidence: 99%
“…Although the bivalves' mean age cannot constrain AT39's potentially oldest mean age, AT39's standard ESR mean age does converge at an mean age of 654 ± 19 ka with an RU model at p = 8, which is a high p value given the tooth's A Σ values and its U concentrations. The maximum possible age for AT39 ranges from 705 ± 20 ka with p = 10 to 800 ± 25 ka at p = 20, both of which also seem unlikely given the associated fauna found at the site [7,18]. Moreover, finding teeth with p ≥ 10 at other sites is rare [19].…”
Section: Dating the Teethmentioning
confidence: 99%
“…With p = 2, AT39's mean age correlates well with MIS 13c (Figure 8). unlikely given the associated fauna found at the site [7,18]. Moreover, finding teeth with p ≥ 10 at other sites is rare [19].…”
Section: Dating the Teethmentioning
confidence: 99%
See 1 more Smart Citation